2019
DOI: 10.1002/aqc.3078
|View full text |Cite
|
Sign up to set email alerts
|

The impact of fisheries management practices on the survival of the Yangtze finless porpoise in China

Abstract: The Critically Endangered Yangtze finless porpoise (Neophocaena asiaeorientalis asiaeorientalis) is facing a significant threat from illegal fishing in Poyang Lake and Dongting Lake, and current fisheries management has proved insufficient to eliminate illegal fishing. A survey of local communities around the two lakes was conducted to investigate fishing activities and their potential impacts. Using a series of six scenarios derived from our data, we suggest that enhanced daytime patrols may have driven fishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
(42 reference statements)
0
16
0
Order By: Relevance
“…Firstly, given the high contribution of C. brachygnathus to the diet of the Yangtze finless porpoise in early and middle March, which is just prior to the commencement of the Chinese annual fishing ban (from March 20 to June 20); we advise extending the regulation of the fish harvest specific to C. brachygnathus in Poyang Lake into the first half of March. Also, we advocate a complete ban on the use of seine nets in March because illegal fishing gear has been the main threat to C. brachygnathus populations, and the widespread use of seine nets can also increase the rates of accidental death of porpoises when animals in starvation are forced to prey on netted fish and can be fatally entangled (Mei et al., 2019). Secondly, we found that semi‐migratory fish are probably the main source of assimilated diets of porpoises over the longer‐term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, given the high contribution of C. brachygnathus to the diet of the Yangtze finless porpoise in early and middle March, which is just prior to the commencement of the Chinese annual fishing ban (from March 20 to June 20); we advise extending the regulation of the fish harvest specific to C. brachygnathus in Poyang Lake into the first half of March. Also, we advocate a complete ban on the use of seine nets in March because illegal fishing gear has been the main threat to C. brachygnathus populations, and the widespread use of seine nets can also increase the rates of accidental death of porpoises when animals in starvation are forced to prey on netted fish and can be fatally entangled (Mei et al., 2019). Secondly, we found that semi‐migratory fish are probably the main source of assimilated diets of porpoises over the longer‐term.…”
Section: Discussionmentioning
confidence: 99%
“…Poyang Lake, one of the lakes adjoining the main stem of the Yangtze River, is currently habitat for approximately 450 wild Yangtze finless porpoises (Huang et al., 2020). Although the number of porpoises in Poyang Lake has remained stable in the past decade (Mei et al., 2019), fishery resources are being gradually reduced by intensified fishing activities and widespread illegal fishing (Wang et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The finless porpoise was observed to be more abundant closer to the HK area than in other areas either in Poyang Lake or in other river sections in the lower reach of the Yangtze River (Kimura et al, 2012;Mei et al, 2019). For example, there were 206 finless porpoise individuals during the low water period of the 2014 winter in Poyang Lake, of which approximately 174 were observed in the HK area near the main channel (Xu, 2015).…”
Section: Hemibarbus Maculatusmentioning
confidence: 99%
“…In addition, the baiji has not been observed in the Yangtze River since 2006 (Turvey et al, 2007), and populations of the finless porpoise have declined severely in the last two decades (Mei et al, 2012). A shortage of fish prey resources was suggested as one of the major reasons inducing the decline of the finless porpoise populations (Wang, 2009;Mei et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…2012; Mei et al . 2019). Over the past 2 decades, the widespread use of personal computers has provided a convenient platform for citizen science projects and contributed to an unprecedented boom in citizen science (Vianna et al .…”
Section: Introductionmentioning
confidence: 99%